Treatment of experimental hyperchloremic metabolic acidosis in horses with enteral electrolyte solution containing sodium acetate - Monteiro, Lorena Chaves; Costa, Caio Monteiro; Ermita, Pedro Ancelmo Nunes; Júnior, Silvio José Printes Gomes; Mattos, Felipe Sperandio; Mansur, Fernanda Campos; dos Santos, Mayara Oliveira; Alves, Samuel Rodrigues; Mafort, Erica Garcia; Fidélis, Cíntia Fernandes; Avanza, Marcel Ferreira Bastos; Teixeira, Raffaella Bertoni Cavalvanti; et al. (Frontiers in Veterinary Science, 2024)
IntroductionIn adult horses, the development and evaluation of enteral electrolyte solutions containing sodium acetate for correcting hyperchloremic metabolic acidosis are still lacking, although these electrolyte and acid–base imbalances are commonly observed. The objective of this study was to evaluate the alkalinizing effect of two enteral electrolyte solutions containing different concentrations of acetate, administered via nasogastric tube in continuous flow, in adult horses with experimental hyperchloremic metabolic acidosis.MethodsSix mares aged between 3 and 10 years were used in a 6×2 crossover design, with each animal receiving both treatments. The horses were subjected to a protocol to induce hyperchloremic metabolic acidosis. They then received one of two treatments: HighAcetate (81.4 mmol/L) and LowAcetate (22.7 mmol/L) at an infusion rate of 15 mL/kg/h for 12 h. Plasma, serum, and urinary biochemical assessments; hematocrit; urinary volume, pH, and specific gravity; and blood gas analysis were measured at the following time points: T-12 h (beginning of the 12-h fast), T0h (end of fasting and beginning of the acidosis induction phase), every 2 h during the hyperchloremic metabolic acidosis induction phase (Ti2h and Ti4h), every 2 h during the 12-h enteral hydration phase (Tt2h, Tt4h, Tt6h, Tt8h, Tt10h, and Tt12h), with one sample taken at T24h (24 h after the start of acidosis induction) and another at T36h (36 h after the start of acidosis induction). Data were analyzed using descriptive statistics and analysis of variance based on a factorial design of repeated measures, with Tukey’s post-hoc test or the Kruskal-Wallis test with Dunn’s post-hoc test for non-parametric tests.ResultsAt the end of the induction phase, the animals developed moderate to severe hyperchloremic metabolic acidosis. The HighAcetate solution effectively corrected electrolyte and acid–base imbalances before the end of the treatment phase (Tt12h), while the LowAcetate solution was not effective in correcting those changes.ConclusionThe HighAcetate (81.4 mmol/L) solution is deemed an effective and safe alternative for the treatment of hyperchloremic metabolic acidosis in horses.